EFL LEARNERS' EXPERIENCES OF PEER FEEDBACK IN PARAGRAPH WRITING THROUGH CLOUD COLLABORATION - Dedi Kurniawan; Hariswan Putera Jaya; Alhenri Wijaya (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTOnline peer feedback has become common in university writing classrooms due to the availability of computer technology. This study aimed to explore EFL learners' experiences engaged in online peer feedback on writing through cloud collaboration. This study was an extension activity of the paragraph writing class for two weeks, in which ten participants voluntarily took part in it and were monitored by two instructors. The peer feedback exchanges, text revisions, and comments from interviews were qualitatively analyzed, and the emerging patterns of interaction were quantified. The results showed that the involvement of the participants in online peer feedback via cloud collaboration facility enabled students to detect and comprehend numerous writing problems, as well as revise and improve their work; both revision and non-revision-oriented feedbacks are part of the overall online textual interaction and communication that can be used to help them develop their second language; and the students also expressed different perspectives about whether they appreciated or disliked their online peer feedback experience. This study also provided some implications and recommendations for further research.ABSTRAKUmpan balik teman sebaya secara online telah menjadi hal yang umum di ruang kelas menulis di universitas sebagai hasil dari ketersediaan teknologi komputer. Penelitian ini bertujuan untuk mengeksplorasi pengalaman pelajar EFL yang terlibat dalam umpan balik teman sebaya secara online dalam menulis melalui kolaborasi cloud. Penelitian ini merupakan kegiatan perpanjangan dari kelas menulis paragraf selama dua minggu yang diikuti oleh sepuluh peserta secara sukarela, dan dipantau oleh dua orang instruktur. Pertukaran umpan balik dari teman sebaya, revisi teks, dan komentar dari wawancara dianalisis secara kualitatif dan pola interaksi yang muncul dikuantifikasi. Hasil penelitian menunjukkan bahwa keterlibatan para peserta dalam umpan balik teman sebaya secara online melalui fasilitas kolaborasi cloud memungkinkan siswa untuk mendeteksi dan memahami berbagai masalah dalam menulis, serta merevisi dan memperbaiki pekerjaan mereka; umpan balik yang berorientasi pada revisi dan non-revisi merupakan bagian dari keseluruhan interaksi dan komunikasi tekstual online yang dapat digunakan untuk membantu mereka mengembangkan bahasa kedua mereka; serta perspektif individu yang berbeda mengenai apakah mereka menyukai atau tidak menyukai pengalaman umpan balik teman sebaya secara online. Penelitian ini juga memberikan beberapa implikasi dan rekomendasi untuk penelitian lebih lanjut.How to Cite: Kurniawan, D., Jaya, H.P., Wijaya, A. (2023). EFL Learners' Experiences of Peer Feedback in Paragraph Writing Through Cloud Collaboration. IJEE (Indonesian Journal of English Education), 10(1), 37-62. doi:10.15408/ijee.v10i1.25134